Tumor-Infiltrating Immune-Related Long Non-Coding RNAs Indicate Prognoses and Response to PD-1 Blockade in Head and Neck Squamous Cell Carcinoma - Ma, Ben; Jiang, Hongyi; Luo, Yi; Liao, Tian; Xu, Weibo; Wang, Xiao; Dong, Chuanpeng; Ji, Qinghai; Wang, Yu (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) in immune cells play critical roles in tumor cell-immune cell interactions. This study aimed to characterize landscape of tumor-infiltrating immune-related lncRNAs (Ti-lncRNAs) and reveal their correlations with prognoses and immunotherapy response in head and neck squamous cell carcinoma (HNSCC). We developed a computational model to identify Ti-lncRNAs in HNSCC, and analyzed their associations with clinicopathological features, molecular alterations and immunotherapy response. A signature of nine Ti-lncRNAs demonstrated an independent prognostic factor for both overall survival and disease-free survival among the cohorts from Fudan University Shanghai Cancer Center, The Cancer Genome Atlas, GSE41613 and GSE42743. Ti-lncRNA signature scores in immune cells showed significant associations with TP53 mutation, CDKN2A mutation and hypoxia. Inferior signature scores enriched in patients with high levels of PDCD1, CTLA4 and expanded immune gene signature (IGS) scores, who displayed a good response to PD-1 blockade in HNSCC. Consistently, superior clinical response emerged in melanoma patients with low signature scores undergoing anti-PD-1 therapy. Moreover, the Ti-lncRNA signature was a prognostic factor independent of PDCD1, CTLA4 and the expanded IGS score. In conclusion, tumor-infiltrating immune profiling identified a prognostic Ti-lncRNA signature indicative of clinical response to PD-1 blockade in HNSCC.